ARTISTIC FEATURES OF SMALL PROSE OF S. VINCENZ (BASED ON THE WORK “THE MOON FROM ATTIC”) - Suliatytskyy, M. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article reveal question of genre and stylistics variety the prose creation of polish writer S. Vincenz. The literary works display original artist organize of our literature.